Angry rain : a brief memoir - Kenny, Maurice, 1929-2016; Maus, Derek C. (Excelsior Editions, an imprint of the State University of New York Press, 2018)
"Maurice Kenny's career as a writer, teacher, publisher, and storyteller spanned more than six decades, over the course of which he published more than thirty books and became one of the most prominent voices in American poetry. From the early 1970s onward, he was an instrumental part of the resurgence of Native American literature through his celebrated volumes of poetry and work as an editor and publisher with the journal Contact/II and with the Strawberry Press. This bittersweet memoir sets the stage for this rich literary life by recounting its tumultuous "first half ... plus a bit," a time during which he moved through a series of worlds that all left their marks on him. Kenny begins with his early years spent among his family in the small northern New York city of Watertown. After an adolescence marked by both significant awakenings and grievous traumas, Kenny sets out to seek his fortunes and find his poetic voice, landing for a while in the Jim Crow-era South, in St. Louis, in Indiana, and finally back in New York City, where he becomes part of a motley creative realm of performers and poets that offers him both fascinated inspiration and disheartening rejection. These recollections conclude with Kenny's maturation into a poet whose reaffirmed indigenous heritage unified an artistic vision that remained in conversation with a wide range of other themes and traditions until his death in April 2016"--